PENERAPAN DECISION TREE DALAM AGEN CERDAS "UNDA ANAK PINTAR" PERMAINAN EDUKASI MUATAN LOKAL BAHASA BANJAR - Asep Nurhuda; Reza Andrea (Jurnal Ilmiah Matrik, 2020)
The educational game "Unda Anak Pintar" is research and development of a puzzle game, it was designed to sharpen memories. In this game, players must read random letters and make words in the Banjar language. Artificial intelligence is also applied in this research. Using the decision tree, game agents can accompany children to play like teachers. The game agent as a virtual teacher can provide sad and happiness emoticon according to the game environment. The results of this study, AI make educational games more interesting and interactive for children.